Indigenous secularism and the secular-colonial. (April 2022) - Carr, Ryan
Many non-Indigenous people assume that secularism—the belief that religion and politics are and should be different spheres of life—is foreign to Native American experience. This partly explains why the topic of Native conversions in early New England has always been so controversial, since conversion implies the differentiation of religion from politics. Be that as it may, history shows that Indigenous peoples are well acquainted with secularism and have been debating it within their communities for centuries. This essay demonstrates proof of concept for a history of Indigenous secularism via a case study of Samson Occom, whose vision of Indigenous self-determination was informed by secularist ideas about sovereignty and conversion. It also offers a critique of scholarly romanticizations of Indigenous peoples' primordially "holistic" a-secularism. This romanticization is the product of a secular-colonial ideology which presupposes the otherness of Indigenous peoples when it comes to differentiating between religion and politics.